The Effectiveness of Using Multimedia In Improving the Students’ Reading Comprehension in English Text - Anjar Kusuma Dewi; Mashuri Mashuri; Maf’ulah Maf’ulah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The purpose of the study was to determine the effectiveness of the use of multimedia, namely PowerPoint Presentation (PPT) to improve the reading comprehension of students of the Elementary Teacher Study Program (PGSD) in learning Bahasa Inggris 2 course in the even semester of the 2020/2021 school year. Researchers chose one class with a total of 30 students using the purposive sampling technique. In this study, the data collection procedure used tests as the research instrument. The results showed an increase in the average score obtained by students where the mean score of students in the pre-test was 55.6, which increased significantly by 24.1 points to 79.7. and the t-test value is greater than the t-table value. In this study, PPTs are effective in improving the reading ability of PGSD students. PPTs increased students' vocabulary and understanding of the general structure of narrative and descriptive texts. PPTs are also efficient in teaching simple past and present tenses.